Legal Authority and Fatwa Convergence in Islamic Finance: A Comparative Study of DSN-MUI and SAC Malaysia - Sundari Arum Kusumawati; Abdul Rahman Prakoso; Putri Indriyani (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
The rapid expansion of the global Islamic finance industry necessitates greater convergence of sharia economic fatwas to ensure legal certainty, regulatory harmonization, and investor confidence across jurisdictions. Divergent institutional authorities and enforcement mechanisms in different countries often result in fragmentation and regulatory inconsistency. This study aims to comparatively analyze the roles and legal authority of Indonesia’s Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) and Malaysia’s Shariah Advisory Council of Bank Negara Malaysia (SAC), and to assess their contributions to global fatwa standardization. Employing a normative juridical method with statutory, conceptual, and comparative approaches, this research relies on secondary data including national regulations, institutional fatwas and resolutions, and international standards issued by Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and Islamic Financial Services Board (IFSB). The findings reveal that DSN-MUI emphasizes adaptive ijtihad and theological legitimacy, yet the binding force of its fatwas depends on regulatory incorporation into national legislation. Conversely, the SAC operates within a statutory legal framework that grants binding authority over Islamic financial institutions and courts, thereby ensuring stronger legal certainty and broader international recognition. Both institutions contribute to global standardization through distinct institutional models: DSN-MUI through contextual and innovative fatwa development, and SAC through formal legal authority and structured engagement in international standard-setting forums. This study concludes that effective global fatwa convergence requires a balanced integration of adaptive jurisprudential flexibility and robust juridical authority through strategic inter-institutional collaboration.